2016
DOI: 10.1136/bjophthalmol-2016-309694
|View full text |Cite
|
Sign up to set email alerts
|

Changes of choroidal structure after intravitreal aflibercept therapy for polypoidal choroidal vasculopathy

Abstract: The binarisation of the EDI-OCT images can be used to quantify the activity of PCV and to predict the prognosis after IVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…14 In addition, the choroidal vascular area (luminal area) was positively correlated with the total choroidal thickness, consistent with our findings. These authors showed that there was no difference in choroidal vasculature or choroidal thickness between active and resolved eyes with CSC, which is also consistent with our results; however, some other authors have reported that the outer choroidal vascular dilatation was reduced after anti-VEGF therapy 29 or PDT. 15 Our results showed that both choroidal vasculature and stromal components remained unchanged in patients with CSC or PNV after anti-VEGF treatment during a relatively short-term follow-up period (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…14 In addition, the choroidal vascular area (luminal area) was positively correlated with the total choroidal thickness, consistent with our findings. These authors showed that there was no difference in choroidal vasculature or choroidal thickness between active and resolved eyes with CSC, which is also consistent with our results; however, some other authors have reported that the outer choroidal vascular dilatation was reduced after anti-VEGF therapy 29 or PDT. 15 Our results showed that both choroidal vasculature and stromal components remained unchanged in patients with CSC or PNV after anti-VEGF treatment during a relatively short-term follow-up period (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…There have been few studies to-date to examine the longitudinal changes in the detailed sub-components of the choroid. In a recent study by Daizumoto and coauthors 23 , they subdivided the choroidal layers into inner and outer layers at the subfoveal 1500 µm region. In 40 treatment-naïve PCV patients, they found that the inner choroid SA and outer choroid LA decreased significantly at month 3 and month 12 after intravitreal aflibercept.…”
Section: Discussionmentioning
confidence: 99%
“…20 In eyes from diabetic patients and eyes with exudative AMD, there were decreased CVI with no significant change in CT. 26,28,29 CVI was also shown to provide additional information to CT in terms of longitudinal choroidal structural changes in diseases such as panuveitis 20 ; Vogt-Koyanagi-Harada (VKH) disease 25 ; central serous chorioretinopathy (CSCR) 24 ; and myopic choroidal neovascularization. 27 Changes in L/C ratio or a similar index called L/S ratio (ratio of choroidal luminal area to stromal area) were investigated and found to yield valuable information in normal physiologic conditions including diurnal variation 22 and dynamic exercise 23 as well as in a number of ocular diseases including exudative AMD 21 ; polypoidal choroidal vasculopathy (PCV) 34 ; CSCR 32,33 ; VKH disease 30,31 ; and retinitis pigmentosa. 36 In this study, we compared the agreement between markers of choroidal vascularity (CVI and L/C ratio) measured by twoimage binarization techniques and significant differences were found between the two measurements.…”
Section: Discussionmentioning
confidence: 99%